Analysis of IFN-gamma and IL-10 Levels as Markers of Inflammation and Response Therapy of Anti-Tuberculosis in MDR Lung TB Patients - Setyawati, Herni; Soedarsono, Soedarsono; Yulistiani, Yulistiani; Fatmawati, Umi (Folia Medica Indonesiana, 2019)
Multidrug-Resistant Tuberculosis (MDR TB) is caused by an organism that is resistant to at least isoniazid and rifampisin, the two most potent TB drug. Immune response to against Mycobacterum tuberculosis infection is related to the function of immunity. The function of interferon-Î³ (pro-inflammatory) is to activate macrophages, to stimulate antimicrobial molecules (to reactive oxygen species and nitric oxide), and to inhibits interleukin-10. Interleukin-10 function is to triggers humoral immunity, to inhibit IFN- Î³. This study aimed to analyze level changes and the correlation with clinical data, also months of MDR TB patients who received standard OAT therapy. This was an observational study using cross sectional design. There were 29 patients who received standard MDR TB OAT therapy from 1-24 months, who met the inclusion criteria. Then, the patients were divided based on duration of the therapy, which are the initial/intensive and advanced phase. The initial phase divided into 2: first one is for 1-4 months therapy's time (5 patients) and the second one is for more than 4-8 months (6 patients). Then, the advanced group divided into two groups again, which are third group with more than 8-16 months (13 patients) and fouth group with more than 16-24 months (5 patients). Then, measured serum concentration IFN-Î³, IL-10 at the start of the study and 4 weeks later with the ELISA method. This research during the period July-December (6 months). IFN-Î³ post concentrations were decreased by 39.14 ± 139.12 pg/mL (p > 0.05). The concentration of IL-10 was decreased by 33.93 ± 109.20pg/mL (p>0.05). Based on the TB score bandim method during pre and posts results were 1 patient experienced severity change from severity class 1 to 2, 1 patient from severity class 2 to 1, 1 patient remained in severity 2 and 26 patient remained in severity 1. The results showed that serum IFN-Î³ and IL-10 levels in initial/intensive and advanced phase patients who received MDR TB regiment after four weeks did not changed,